Urgensi Mahar Dalam Perkawinan Perspektif Kompilasi Hukum Islam - Cici Handayani Mangunsong; Faisar Ananda Arfa (Peneliti.net, 2023)
A dowry is a gift that a husband must give to a wife as a gift that can be in the form of money, jewelry or services such as teaching the Qur'an as long as it does not conflict with Islamic law. Although this dowry is required to be paid by the bridegroom-to-be, this dowry is not a pillar that exists in the marriage law. Because this dowry is not a pillar, the dowry is sometimes not seen as important for the future husband. The purpose of this study is to explain how important the dowry is for the bride-to-be which has been regulated in articles 30 to 38 of the KHI on dowry. This type of research is library research, namely all efforts made by the author to obtain or collect all information relevant to the problem under study. The data found are then discussed and analyzed inductively to produce conclusions. The next step is for researchers to explain the articles contained in the KHI related to dowry. The result and discussion that the dowry is an obligation that must indeed be given by the prospective bridegroom either directly or suspended.